2011
DOI: 10.1038/npp.2011.81
|View full text |Cite
|
Sign up to set email alerts
|

Moderation of Adult Depression by a Polymorphism in the FKBP5 Gene and Childhood Physical Abuse in the General Population

Abstract: Childhood maltreatment and depressive disorders have both been associated with a dysregulation of the hypothalamic-pituitary-adrenal axis. The FKBP5 gene codes for a co-chaperone regulating the glucocorticoid-receptor sensitivity. Previous evidence suggests that subjects carrying the TT genotype of the FKBP5 gene single-nucleotide polymorphism (SNP) rs1360780 have an increased susceptibility to adverse effects of experimental stress. We therefore tested the hypothesis of an interaction of childhood abuse with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
155
1
4

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(174 citation statements)
references
References 33 publications
14
155
1
4
Order By: Relevance
“…Similarly, elevated glucocorticoid levels have been associated with larger amygdala volumes (Buss et al 2012;Lupien et al 2011). Considering a heightened amygdala response and a larger volume as possible endophenotypes for stress-related disorders, the present findings are in line with previous reports suggesting an important role of the FKBP5 T allele in mood disorders (Appel et al 2011;Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and PTSD (Binder et al 2008).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Similarly, elevated glucocorticoid levels have been associated with larger amygdala volumes (Buss et al 2012;Lupien et al 2011). Considering a heightened amygdala response and a larger volume as possible endophenotypes for stress-related disorders, the present findings are in line with previous reports suggesting an important role of the FKBP5 T allele in mood disorders (Appel et al 2011;Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and PTSD (Binder et al 2008).…”
Section: Discussionsupporting
confidence: 82%
“…In line with this, rs1360780 has been associated with psychopathology such as mood disorders (Binder et al 2004;Lavebratt et al 2010;Lekman et al 2008;Zobel et al 2010) and suicidality (Brent et al 2010). Moreover, this SNP has been shown to interact with childhood abuse in predicting PTSD symptoms (Binder et al 2008) and susceptibility to depression (Appel et al 2011), with an increased risk in the TT genotype following childhood abuse.…”
Section: Introductionmentioning
confidence: 76%
“…Taken together with previous reports, it appears that hippocampal sensitivity to stressors and subsequent cortisol fluctuations leads to decreased hippocampal functioning and possibly reduced hippocampal volume. All these findings, along with a number of other recent observations (Xie et al, 2010;Zimmermann et al, 2011;Appel et al, 2011;Buchmann et al, 2014), suggest a model in which the FKBP5 genotype is associated with enhanced intermediate neural and behavioral phenotypes that may underlie increased risk for PTSD and other stress-related psychiatric illnesses following trauma exposure.…”
Section: Introductionmentioning
confidence: 93%
“…Lifetime diagnoses were assigned according to diagnostic hierarchy rules and exclusion criteria as stated in the DSM-IV-TR. Further details on sampling, assessment procedures and quality assurance are reported in detail elsewhere 40 .…”
Section: Samplesmentioning
confidence: 99%
“…The sample comprised 160 individuals reporting panic attacks (female=103, male=57; mean age 51.4±12.0; of those, 74 met diagnostic criteria of PD with or without agoraphobia [female=54, male=20; mean age 50.9±11.1]) and their sex-matched healthy controls (n=160; female=101, male=59; mean age 51.4±12.0). All participants were drawn from a follow-up examination of 6,267 participants of the epidemiological Study of Health in Pomerania (SHiP), reported in detail elsewhere 40,41 . Criteria of a panic attack or confirmed PD were assessed using a standardized computerassisted personal version of the Munich Composite International Diagnostic Interview (M-CIDI; 42 ).…”
Section: Samplesmentioning
confidence: 99%